STUDY OF EFFECTIVENESS OF PERFORMANCE APPRAISAL SYSTEM IN SELECTED INDIAN COMPANIES - Jindal, Shivali; Laveena; Navneet (International Journal of Research -GRANTHAALAYAH, 2015)
An evaluation of previous performance is experienced by the vast majority of recruits each year. The management of performance level is the sum up of performance appraisal systems. This is a continuous and interactive process designed to motivate employees, and check their capability with the main motive to facilitate productivity. The performance management systems involve various activities which are much more than simply reviewing what an employee has done. This research paper is all about understanding the need of performance management systems, ways in which performance appraisals can be constructed, the occurrence of potential problems, benefits which could be availed and the information of the progress.